An Evaluation of the Effects of Motivation, Satisfaction on Destination Loyalty: Case Study Tourism Malaysia - Shukor, Md Shafiin; Mohd Salleh, Norlida Hanim; Mohd Idris, Siti Hajar (International Journal of Social Sciences and Management, 2017)
In tourism literature, stimulation of motivation on tourist journey is one of the vital aspect. This study analyzed the satisfaction and loyalty based on a sample of 200 respondents from four regions, namely Southeast Asia, West Asia, Europe and America. The selection of four regions was due to several reasons which are, i) market for Southeast Asia is the leading supplier of arrivals, ii) Western Asian markets showed an increase in the arrival of the high impact of the September 11th incident, iii) European and American Markets were to represent the market of developed countries. This study, based on the method of Strutural Equatation Model (SEM) using Statistical Package for Social Science version (SPSS 21.0) and Analysis of Moment Structures 5 (AMOS 5) as a tool of analysis. SEM methods used to test the analysis of cause, and effect variables are independent and dependent variables as well as specific information to estimate the structural equation model based on variance value. It was used to test Exploratory Factor Analysis (EFA) and AMOS 5 used to test Confirmatory Factor Analysis (CFA). Results of this study found that the assessment made by foreign visitors to the Malaysia tourism products and services is positive. As a result, the experience will create loyalty to Malaysia's tourism industry in the form of repeat visits (β: 0.547, t-test: 7.472 ***) and promote the destination to friends and relatives that have the potential to make visits (β: 0.794, the t-test: 8.623 ***). However, it was found that the value of the coefficient of regression for stimulus push is low for satisfaction (β: 0.228, t-test: 1.976 **). This findings could be used as guidance to the authorities and operators, policy makers in knowing real satisfaction that stimulates tourist arrivals to Malaysia. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 137-147